2014
DOI: 10.1162/jocn_a_00652
|View full text |Cite
|
Sign up to set email alerts
|

All Competition Is Not Alike: Neural Mechanisms for Resolving Underdetermined and Prepotent Competition

Abstract: People must constantly select among potential thoughts and actions in the face of competition from (a) multiple task-relevant options (underdetermined competition) and (b) strongly dominant options that are not appropriate in the current context (prepotent competition). These types of competition are ubiquitous during language production. In this work, we investigate the neural mechanisms that allow individuals to effectively manage these cognitive control demands and to quickly choose words with few errors. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 49 publications
3
29
0
Order By: Relevance
“…Similarly, Martin and Cheng (2006) showed that patients with VLPFC damage were not impaired in generating a verb in response to a noun probe as long as the two were highly associated, even if multiple possible answers were possible. For example, both “apple” → eat, and “door” → close/open were easier for VLPFC patients compared to “rug” → roll, lay, walk, etc., even though “apple” was strongly associated with only one verb, and “door” with more than one (see also Snyder, Banich, & Munakata, 2014). The authors argued that these results pointed to VLPFC’s role in strengthening associations, as opposed to selection among alternatives.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Similarly, Martin and Cheng (2006) showed that patients with VLPFC damage were not impaired in generating a verb in response to a noun probe as long as the two were highly associated, even if multiple possible answers were possible. For example, both “apple” → eat, and “door” → close/open were easier for VLPFC patients compared to “rug” → roll, lay, walk, etc., even though “apple” was strongly associated with only one verb, and “door” with more than one (see also Snyder, Banich, & Munakata, 2014). The authors argued that these results pointed to VLPFC’s role in strengthening associations, as opposed to selection among alternatives.…”
Section: Discussionmentioning
confidence: 95%
“…This is compatible with VLPFC activity affecting the drift rate by boosting the associations between the bottom-up cues and the target. It is noteworthy that variations in the drift rate may also reflect “top-down attention” (e.g., Bogacz et al, 2006; p.731), but implementation of top-down attention seems to be more aligned with the role of dorsolateral PFC (e.g., Snyder, et al, 2014). …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, if the critical semantic control hub were in the IFG/VLPFC grey matter, then multimodal semantic deficits should have been most strongly associated with damage to that region rather than to the underlying white matter as we observed. In fact, stroke damage to the left IFG/VLPFC has been associated with a more specific deficit of lexical selection in the context of semantic competition (e.g., Mirman & Graziano, 2013; Schnur et al, 2006, 2009; for related fMRI evidence see also Snyder, Banich, & Munakata, 2014). Second, although some of the tests that loaded strongly on the Semantic Recognition factor have substantial semantic control demands (e.g., Camel & Cactus Test), others do not (e.g., Semantic Category Discrimination is a simple AX semantic discrimination task), so it is not simple to argue that the Semantic Recognition factor was rather a Semantic Control factor.…”
Section: Discussionmentioning
confidence: 99%